2017
DOI: 10.1002/2017gl074602
|View full text |Cite
|
Sign up to set email alerts
|

Net community production in the bottom of first‐year sea ice over the Arctic spring bloom

Abstract: The balance of photosynthesis and respiration by organisms like algae and bacteria determines whether sea ice is net heterotrophic or autotrophic. In turn this clarifies the influence of microbes on atmosphere‐ice‐ocean gas fluxes and their contribution to the trophic system. In this study we define two phases of the spring bloom based on bottom ice net community production and algal growth. Phase I was characterized by limited algal accumulation and low productivity, which at times resulted in net heterotroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 56 publications
5
20
1
Order By: Relevance
“…This was evident by the high explained variance of NPP by bottomice light, the similarity of NPP and transmittance correlogram curves, and the coincidence of high NPP patches with high light transmittance. Similar to a recent study by Campbell et al (2017) that demonstrated a disjoint in ice algal carbon biomass and NPP over the spring to summer transition period, our chl a biomass patches did not always follow the light and NPP regimes, which clearly illustrates one key difference between the spring and summer ice algal communities.…”
Section: Sea Ice Ridgessupporting
confidence: 71%
“…This was evident by the high explained variance of NPP by bottomice light, the similarity of NPP and transmittance correlogram curves, and the coincidence of high NPP patches with high light transmittance. Similar to a recent study by Campbell et al (2017) that demonstrated a disjoint in ice algal carbon biomass and NPP over the spring to summer transition period, our chl a biomass patches did not always follow the light and NPP regimes, which clearly illustrates one key difference between the spring and summer ice algal communities.…”
Section: Sea Ice Ridgessupporting
confidence: 71%
“…Mundy, unpublished data), which was dominated by the pennate diatom N. frigida and the centric diatom Attheya sp. (Campbell et al, 2017). Thus, it is possible that the onset of the bloom was seeded in part by ice algae sloughing from the ice bottom.…”
Section: Uibs Triggered By Extreme Meteorological Eventsmentioning
confidence: 99%
“…Within the sea ice, net heterotrophy and remineralization (Fripiat et al, 2017) has been observed at certain times in the year. However, Campbell et al (2017) showed that Arctic sea ice switches from net heterotrophy to net autotrophy during the period of rapid algal accumulation, which corresponds to the month of May in our study (Figure 8). It therefore seems most likely that the DIC accumulation we observed under the ice was driven by respiration in the water column.…”
Section: 1029/2018jc013899mentioning
confidence: 99%